Significance of Seaweed Liquid Fertilizers for Minimizing Chemical Fertilizers and Improving Yield of Arachis hypogaea under Field Trial - Ramasamy Rengasamy2, Sekaran Sridhar1* (Recent Research in Science and Technology, 2010)
Efficacy of different concentrations of Seaweed Liquid Fertilizers (SLFs) obtained from the brown seaweed Sargassum wightii Grev. and green seaweed Ulva lactuca L, was made on Arachis hypogaea under field trial. Combined effect of 1.0% SLF(s) plus different proportions of recommended rate of chemical fertilizers was also made on A. hypogaea. Among the different concentrations of SLF(s) investigated, the plants that received with 1.0% SLF showed maximum fresh weight, dry weight, root and shoot length, number of branches, leaf area and content of total chlorophyll, chlorophyll a and b, protein, carbohydrate, lipid and yield. Similarly the plants that applied with 1.0% SLF(s) plus 50% recommended rate of chemical fertilizers showed enhanced characteristics. Arachis hypogaea treated with 1.0% SLF of S. wightii / U. lactuca plus 50% recommended rate of chemical fertilizers showed an increased yield up to ca. 4.1Kg fresh weight which was more than 11% to that of the plants received with 100% recommended rate of chemical fertilizers. The two SLFs were also analyzed for micro and macro elements and the plant growth regulators like auxin and cytokinin.